Dynamics of Religious Moderation: Analytical Study of Islamic Religious Education Learning in Junior High Schools - Afriantoni Afriantoni; Armelis Armelis; Aisyah Khairunnisa; Taufik Alhidayah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to analyze religious moderation in the context of Islamic Religious Education learning at Junior High School and the strategies applied in implementing religious moderation. This research uses a qualitative descriptive approach with data collection techniques through observation and semi-structured interviews. The research was carried out at Junior High School, which has heterogeneous students with different religious and ethnic backgrounds. The SWOT analysis results show that strength lies in the independent curriculum and teacher competence in religious moderation. However, weaknesses arise from limited resources and teachers' theoretical understanding. Opportunities lie in awareness of the diversity of Indonesian society and support from external parties such as the Religious Harmony Forum (FKUB). The threat comes from resistance to religious moderation and information imbalance. The implementation of religious moderation in Islamic Religious Education learning has great potential. Strengthening teacher training, collaborating with external parties, and utilizing educational technology are strategies that can be taken to overcome challenges. These steps are expected to improve the quality of learning and form moderate character in students.